1997
DOI: 10.1080/014461997373132
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing construction time and cost overruns on high-rise projects in Indonesia

Abstract: Many variables have an impact upon construction time and cost overruns in Indonesia. A questionnaire survey was undertaken of project managers working on high-rise construction projects in two Indonesian cities: Jakarta and Yogyakarta. The variables identified were ranked according to their perceived importance and frequencies of occurrence. Inflationary increases in material cost, inaccurate material estimating and project complexity are the main causes of cost overruns. The predominant causes of delay are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
358
4
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 528 publications
(397 citation statements)
references
References 11 publications
13
358
4
22
Order By: Relevance
“…According to Kaming et al (1997) , one of the most important factors causing delays in high-rise projects in Indonesia is the shortage of resources. In addition, Noulmanee et al (1999) investigated the causes of delays in highway construction in Thailand and concluded that one of the main causes of delays is the insuffi cient resources of an organisation.…”
Section: Insuffi Cient Fi Nancial Resourcesmentioning
confidence: 99%
“…According to Kaming et al (1997) , one of the most important factors causing delays in high-rise projects in Indonesia is the shortage of resources. In addition, Noulmanee et al (1999) investigated the causes of delays in highway construction in Thailand and concluded that one of the main causes of delays is the insuffi cient resources of an organisation.…”
Section: Insuffi Cient Fi Nancial Resourcesmentioning
confidence: 99%
“…Josephson et al [42] note the contributing factors of design to rework in Swedish construction industry are lack of co-ordination, unsuitable design, faulty design and incomplete drawings. Kaming et al [14] describe the magnitude of design changes depend upon pre-design site investigation, the completeness of working drawings available at the time of proposal and unpredictable circumstances during construction. Consultant's inability [55], design omission [15], [27], incomplete drawings [17], design errors [51] and quality of design [44] caused cost and schedule increases.…”
Section: Design-related Causesmentioning
confidence: 99%
“…Although design change has tremendous negative effects [64], attention paid to proactively manage the impact of these changes is limited [65]. There has been considerably research undertaken that has sought to determine the causes of time delays and cost overruns in construction projects [6], [14], [18], [22], [56], [63], [66]- [69]. Research into determining the causes of time delays and cost overruns has reached saturation point; consistently the same causal variables are identified.…”
Section: Impacts To Project Time and Cost Performancementioning
confidence: 99%
See 2 more Smart Citations